Screening rice (Oryza sativa L.) genotypes for resistance against drought - Salleh, Mohd Syahmi; Malek, Ris Amirah; Shahari, Rozilawati; Nordin, Mohd Shukor (Zibeline International, 2020)
Drought is regarded as one of the limiting factors in rice production nationally and globally. The present study was conducted to study morpho-physiological and biochemical responses of rice genotypes to drought stress, to identify potential traits for use as a selection criterion in breeding drought-tolerant rice at seedling stage and finally to identify rice genotype resistant to drought stress for use as parents in future breeding. The experimental design used was a split-plot design with three replications, with drought stress as the main plot and rice genotypes as the sub-plot. The main plots consisted of control (normal irrigation) and drought stress. The sub-plots consisted of twelve rice genotypes namely Apami (V1), Boewani (V2), Basmati 370 (V3), Cica-4 (V4), Dular (V5), Jarom mas (V6), Kalarata (V7), Biris (V8), Haiboq (V9), Moroberekan (V10), MR 297 (V11) and Aerob 1 (V12). Results showed that drought stress led to a decrease in plant height, leaves size, root length, total dry weight, and number of leaves but an increment in proline content. The genotype Apami and Kalarata were found to accumulate higher proline content indicating potential resistant ability towards drought stress. Dular and Aerob1, along with tolerant control genotype, Moroberekan, on the other hand, recorded a lower SES score. Leave size, root length, and plant height could also be used as a selection criterion in breeding drought-tolerant rice due to high values of broad-sense heritability and genetic advance by percentage of mean (GAM). Nevertheless, further study on the genetics and physiological basis of tolerant ability at reproductive growth stages are necessary in order to assess grain yield potential of the potentially tolerant genotype reported in this study.